Load carriage analysis for military using functional data analysis technique : registration and permutation test - Wan Din, Wan Rozita; Rambely, Azmin sham; Jemain, Abdul Aziz (International Journal of Basic and Applied Sciences, 2014)
This paper focused on the analysis of ground reaction force (GRF) of load carriage for military through functional data analysis (FDA) technique. The main objective of the study is to investigate the effect of 10% bodyweight (BW) load increment for normal walking through FDA method. The experiment on GRF was carried out by ten healthy military soldiers aged 31 ± 6.2 years old; weighing 71.6 ± 10.4 kg with the height of 166.3 ± 5.9 cm. Data was captured using Vicon 1.4 motion analysis system, Kistler force plates and thirty nine body markers attached to the subjects. FDA method mainly B-spline basis formation, time normalization, smoothing, curves registration and permutation tests were applied to analyze the data. The results confirmed that FDA did provide a better technique of smoothing to produce quality data in an easy manner. From this paper we conclude that registration did significantly align all the curves according to curves features providing a better way of distinguishing the amplitude of load increment. Finally, permutation tests confirmed that 10% BW load increased from 0% BW to 40% BW, have significant effect on soldiers regarding their load carriage and GRF.
Keywords: Military Load Carriage; GRF; FDA; Curve Registration; Permutation Test.